«The primitive communist society and its decomposition»: the prehistorical past of the territory of Belarus by V. K. Shcharbakou - Vaitovich, Aliaksandra U.; Kurlovich , Palina S. (Journal of the Belarusian State University. History, 2020)
The article is devoted to the analysis of the concept of the «primitive communist society» set out by the famous scientist and organizer of science in the 1930s, the first dean of the historical faculty of Belarusian State University V. K. Shcharbakou in his «Essay on the history of Belarus» (1934). This book was the first attempt in native historiography to systematically illuminate the initial period of the history of our country in a marxist manner. The researcher did not set himself the goal of preparing a full-fledged archaeological publication. Creating a synthetic review of the history of Belarus, he included in it only certain topics related to primitive and early medieval archaeology. The scientist’s methodological approaches to the study of ancient history corresponded to the theoretical developments of Soviet historical science in the 1920s – at the beginning of the 1930s, and the work no longer match the new «settings» by the time of release. The authors of the article determined the contribution of V. K. Shcharbakou to the interpretation of the primitive history of Belarus, which allows to understand better the history of Belarusian archaeological and historical thought of the interwar period.